The influence of injection time and holding time on the residual stress state in injection moulded parts - Jaruga, T.; Mazik, K. (Polimery, 2013)
The requirements for the manufacturing process of transparent parts by injection moulding were described. Special attention was paid to such processing parameters like injection time and holding time, which are essential for the production of good quality parts. The effect of these parameters on the residual stress in (methyl methacrylate)-acrylonitrile-butadiene-styrene plastic (MABS) injection moulded parts was investigated using photoelastic analysis.